Odpowiedzi

2010-02-05T19:44:50+01:00
3x-2(y-x)=-(2x-1)
x-½-2=y+x/3

3x-2y+2x=-2x+1
y=x-½-2-x/3

3x+2x+2x=2y+1
y=2/3x-5/2

7x=2*(2/3x-5/2)+1
y=2/3x-5/2

7x=4/3x-5+1
y=2/3x-5/2

7x-4/3x=-4
y=2/3x-5/2

21/3x-4/3x=-4
y=2/3x-5/2

17/3x=-4
y=2/3x-5/2

x=-12/17
y=2/3*(-12/17)-5/2

x=-12/17
y=-8/17-5/2

x=-12/17
y=-16/28-85/28

x=-12/17
y=-101/28
2010-02-05T19:58:22+01:00
2010-02-05T19:58:45+01:00
3x-2(y-x)=-(2x-1)
x-½-2=y+x/3

3x-2y+2x = -2x +1
x-2,5 = y+x/3 // *3

5x-2y= -2x+1
3x- 7,5= 3y+ x

5x-2y +2x=1
3x - 3y - x = 7,5

7x-2y=1//*3
2x-3y=7,5//*(-2)

{21x-6y=3
{-4x+6y=-15

17x=-12//:17
x= -12/17

21 * (-12/17) - 6y = 3
-256/17-6y=3
-6y=3+256/17
-6y= 307/17 //:(-6)
y= -307/102

??